Exploring a Family-First Approach in Addiction Treatment: A Conceptual Shift. - Browning, Scott; Schneider, Liora (American Journal of Family Therapy, 2026)
Typically, addiction treatment starts by focusing on the individual, and family therapy is added later as a supplementary element. This order frequently puts the family in a passive role, reliant on the individual's willingness to participate in the recovery process. This paper introduces a method that draws special attention on empowering the family to encourage the individual with addiction to seek treatment. Addiction operates within a system, and by focusing on the family system the chances of a more permanent recovery increase. The various stages of addiction are linked to the needs of the family during those periods. As shown in the case study, the journey to recovery is challenging and non-linear. At times, progress feels steady, while other moments family members and the individual with addiction fall back into old patterns and unhealthy interactions. However, as highlighted in this case, helping a family come to understand that they are part of a strong support network. Family therapy and strong commitment to the fellowships gives the addicted individual a fighting chance to achieve recovery.